(untitled) (Herald of Journalism, 2016)
The article is prepared in the term of work results of materials for 2012–2014 years research on the topic 1899/GF2 ‘Elaboration of humanitarian technologies in formation of social consciousness of a citizen of an intellectual society’. The project is realized in the framework of the project of the grant financing of scientific researches of the Ministry of Education and Science of the RK.